Comparison of the tourism in Vienna and Budapest - Hlatká, Adéla; Netková, Jarmila; Lautnerová, Anna; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2014)
This thesis deals with tourism in Vienna and in Budapest. The aim of the thesis is to find similarities and differences between tourism in these two cities. First of all types of tourism dominant in these cities are described. The following chapters analyzes information and data regarding these metropolises. Focus is given to realization and localization presumptions of tourism. Collected data are compared and finally SWOT analysis are made to evaluate tourism in Vienna and in Budapest and to find ways that could improve position of these capitals on tourism market.
Vedoucí práce: Jarmila Netková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: cestovní ruch [obor dipl. práce]; diplomové práce; master's theses